PENGARUH PENGGUNAAN GAME ONLINE MOBILE LEGENDS BANG-BANG TERHADAP AKHLAK PESERTA DIDIK KELAS XI DI SMA NEGERI 3 BAUBAU - Ainun Amaliah, Nurul; Basri, Basri; Jusu, La (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The development of science and technology has produced various new discoveries, including in the field of digital games. Online games are electronic and visual-based games that are increasingly popular among students as entertainment when they feel bored with learning. One of the most popular games today is Mobile Legends Bang-Bang. The use of this game may have both positive and negative impacts depending on how it is played. This research aims to determine the influence of playing Mobile Legends Bang-Bang on students’ moral behavior. The method used is quantitative research with purposive sampling as the technique for selecting samples. The data were collected through observation, questionnaires, and documentation. Data were analyzed using validity tests, reliability tests, prerequisite tests, hypothesis testing, and simple linear regression. The results show that the use of Mobile Legends has an influence on students’ moral behavior, based on a t-value of 0.06 with a significance of 0.995 > 0.05, indicating that the game affects the moral character of eleventh-grade students at SMA Negeri 3 Bau-Bau